Overview of Metamaterials-Integrated Antennas for Beam Manipulation Applications: The Two Decades of Progress - Bashar A. F. Esmail; Slawomir Koziel; Lukasz Golunski; Huda Bin A. Majid; Rusan Kumar Barik (IEEE Access, 2022)
Metamaterials (MMs) are synthetic composite structures with superior properties not found in naturally occurring materials. MMs have gained massive attention over the last two decades because of their extraordinary properties, such as negative permittivity and permeability. These materials enable many applications in communication subsystems, especially in the field of antenna design, to enhance gain, bandwidth, and efficiency, reduce the size, and deflect the radiation pattern. The demand for beam-deflection antennas is significant in modern wireless communication research studies due to their importance in enhancing service quality, system security, avoiding interference, and economizing power. The MM structures are usually included in the vicinity of the radiating element or incorporated in the antenna substrate for controlling the radiation pattern. This review study provides an introduction to MMs, focusing on their electromagnetic properties, classification, and design approaches. Furthermore, a detailed study of using the MMs to manipulate the radiation is carried out, where different properties such as the positive/negative refractive index, epsilon-near-zero (ENZ), and mu near-zero (MNZ) are employed to achieve a beam-deflection antenna. Reconfigurable MMs are also loaded to the antenna to achieve multi-directional beam deflection with negligible effect on the antenna’s physical size. Moreover, the gradient-index (GRIN) based on MMs is used to obtain high deflection angles with minor effects on other antenna properties.